2020
DOI: 10.1097/jpn.0000000000000513
|View full text |Cite
|
Sign up to set email alerts
|

Fresh Perspectives on Hospital-Acquired Neonatal Skin Injury Period Prevalence From a Multicenter Study

Abstract: The objective of this study was to explore neonatal skin injury period prevalence, classification, and risk factors. Skin injury period prevalence over 9 months and χ 2 , Mann-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 36 publications
(81 reference statements)
0
8
0
Order By: Relevance
“…Mechanical force skin injuries have been identified in the literature as a neonatal complication since the 1980s 1,2 . Neonates are particularly vulnerable to skin injuries related to hospitalised care, with a variety of severities identified in previous studies 3 . Some of these injuries have lasting impacts such as scarring which affects movement and self-esteem for the individual affected 4,5 .…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Mechanical force skin injuries have been identified in the literature as a neonatal complication since the 1980s 1,2 . Neonates are particularly vulnerable to skin injuries related to hospitalised care, with a variety of severities identified in previous studies 3 . Some of these injuries have lasting impacts such as scarring which affects movement and self-esteem for the individual affected 4,5 .…”
Section: Introductionmentioning
confidence: 97%
“…However, while neonates sustain skin injuries from a number of mechanical forces similar to adults, the maturity of neonatal skin puts the application of adult injury scales into question 1,2,7 . A mechanical skin injury is defined as a distortion or injury of the integrity of the skin and/or underlying integumentary structures by external motion 3,6 . Common forces associated with skin injury for the neonatal population include pressure (a source exerting force on the skin), friction (resistance created by surfaces moving between skin and surface), shearing (still outer layers with inner layers moving transversely), tear (blunt force resulting in separation of skin layers) 8,9 and stripping (when adhesive is more strongly bonded to the skin than the intradermal bonds, this is known as medical adhesive-related skin injury [MARSI]) 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A single adhesive removal has been shown to strip 70–90% of a baby’s epidermis (though multiple adhesive replacements can cause deeper injury), as the adherence of tape-to-skin is often stronger than the adherence of skin layers to each other [ 8 ]. Skin injuries are common in the NICU and the majority are unreported, of those reported most are related to the devices used by clinicians to provide patient care [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The risk of neonatal skin injuries in NICU is as high as 43.1 percent [7]. Several large studies performed on newborn infants reported skin breakdown, pressure injuries, and skin-stripping because of the fixation, pressure, and removal of medical adhesives [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%